Heat transfer simulation of various material for polymerase chain reaction thermal cycler / Kenny Lischer … [et al.] - Lischer, Kenny; Digdaya Putra, Ananda Bagus Richky; Sahlan, Muhamad; Khayrani, Apriliana Cahya; Ginting, Mikael Januardi; Wijanarko, Anondho; Whulanza, Yudan; Pratami, Diah Kartika (Universiti Teknologi MARA, 2021)
Medical diagnosis is the initial stage in identifying a person's condition, disease or injury from its signs and symptoms. The diagnostic method is carried out quantitatively by using a diagnostic kit which measures data such as blood pressure, heart rate frequency and blood cell concentration. These diagnostic kits are available in their respective capabilities and their activities require medical facilities and logistical readiness to function. Furthermore, Indonesia's geographical condition which consists of many islands and mountains causes uneven distribution of health facilities and laboratories in each region. Therefore, resulting in problems such as inadequate access and availability of these diagnostic kit in each region. Presently, one of the most widely used diagnostic methods is the Polymerase Chain Reaction (PCR) which allows the amplification of specific fragments from complex DNA. In PCR, only a small amount of DNA is needed to produce enough replication copies which were further analyzed by microscopic examination. This process begins with thermal cycling, which is the reactant's exposure to the heating cycle and repetitive repairs to produce reactions to different temperatures. This study aims to examine the material used for thermal cyclers which is an essential aspect of the heat transfer needed by the PCR process. In this study, heat transfer from several materials were simulated and analyzed by COMSOL Multiphysics 5.3 Software. The following results were obtained from the simulation: the saturation time for heating aluminum, copper and nickel were 29,37 and 51 seconds, respectively. Meanwhile, the cooling time was 26, 35 and 55 seconds, respectively. In addition, the saturation time for heating and cooling silver and Polydimethylsiloxane (PDMS) were 26 and 1480 seconds, respectively.